Low‐frequency heart rate variability is related to the breath‐to‐breath variability in the respiratory pattern. (3rd December 2013) - Beda, Alessandro; Simpson, David M.; Carvalho, Nadja C.; Carvalho, Alysson Roncally S.
Abstract Changes in heart rate variability (HRV) at "respiratory" frequencies (0.15–0.5 Hz) may result from changes in respiration rather than autonomic control. We now investigate if the differences in HRV power in the low‐frequency (LF) band (0.05–0.15 Hz, HRVLF) can also be predicted by respiration variability, quantified by the fraction of tidal volume power in the LF (VLF, n). Three experimental protocols were considered: paced breathing, mental effort tasks, and a repeated attentional task. Significant intra‐ and interindividual correlations were found between changes in HRVLF and VLF, n despite all subjects having a respiratory frequency above the LF band. Respiratory parameters (respiratory period, tidal volume, and VLF, n) could predict up to 79% of HRVLF differences in some cases. This suggests that respiratory variability is another mechanism of HRVLF generation, which should be always monitored, assessed, and considered in the interpretation of HRV changes.